Measurement of Motivation States for Physical Activity and Sedentary Behavior: Development and Validation of the CRAVE Scale - Stults-Kolehmainen, Matthew A.; Blacutt, Miguel; Fogelman, Nia; Gilson, Todd A.; Stanforth, Philip R.; Divin, Amanda L.; Bartholomew, John B.; Filgueiras, Alberto; McKee, Paul C.; Ash, Garrett I.; Ciccolo, Joseph T.; Brotnow Decker, Line; et al. (Frontiers in Psychology, 2021)
Physical activity, and likely the motivation for it, varies throughout the day. The aim of this investigation was to create a short assessment (CRAVE: Cravings for Rest and Volitional Energy Expenditure) to measure motivation states (wants, desires, urges) for physical activity and sedentary behaviors. Five studies were conducted to develop and evaluate the construct validity and reliability of the scale, with 1,035 participants completing the scale a total of 1,697 times. In Study 1, 402 university students completed a questionnaire inquiring about the want or desire to perform behaviors “at the present moment (right now)”. Items related to physical activity (e.g., “move my body”) and sedentary behaviors (e.g., “do nothing active”). An exploratory structural equation model (ESEM) revealed that 10 items should be retained, loading onto two factors (5 each for Move and Rest). In Study 2, an independent sample (n= 444) confirmed these results and found that Move and Rest desires were associated with stage-of-change for exercise behavior. In Study 3, 127 community-residing participants completed the CRAVE at 6-month intervals over two years- two times each session. Across-session interclass correlations (ICC) for Move (ICC = .72-.95) and Rest (ICC = .69-.88) were higher than when they were measured across 24-months (Move: ICC = .53; Rest: ICC = .49), indicating wants/desires have state-like qualities. In Study 4, a maximal treadmill test was completed by 21 university students. The CRAVE was completed immediately pre and post. Move desires decreased 26% and Rest increased 74%. Changes in Move and Rest desires were moderately associated with changes in perceived physical fatigue and energy. In Study 5, 41 university students sat quietly during a 50-minute lecture. They completed the CRAVE at 3 time points. Move increased 19.6% and Rest decreased 16.7%. Small correlations were detected between Move with perceived energy and tiredness, but not calmness or tension. In conclusion, the CRAVE scale has good psychometric properties. These data also support tenets of the WANT model of motivation states for movement and rest (Stults-Kolehmainen et al., 2020). Future studies need to explore how desires to move/rest relate to dynamic changes in physical activity and sedentarism.